Foreign Direct Investments Expansion – Essential Globalization Factor - Cătălin Emilian HUIDUMAC PETRESCU; Radu-Marcel JOIA; Gheorghe HURDUZEU; Liviu Bogdan VLAD (Theoretical and Applied Economics, 2011)

(untitled)
We live in a time when the world economy is constantly changing. Foreign direct investments is one of the most dynamic part of the world economy and in a continuous globalization, those international financial flows determining the traders to know their defining elements and to adopt a specific management in the international affairs field.    We are viewers of an unprecedented expansion of foreign direct investments, essential factor of the globalization development process. The paper analyzes the evolution of FDI so far, along with a brief illustration as the main trends of international financial flows for 2010 and 2011.    In the context of economic globalization, it is absolutely necessary to clear out a study on the various economic activities, especially on the differences between countries. The analysis of these differences is particularly important as it helps improve and optimize the strategies adopted by foreign transnational companies.    In the past 15 years, one observes that most companies in emerging countries, characterized by a great expansion, have adopted in the first phase of their existence, corporate strategies that gave them the opportunity to become global companies. According to surveys, after reaching the first goal, becoming a multinational or a transnational company, they have developed new business models beyond the classical principles and strategies. It is anticipated that in the coming decades, the strategies of emerging companies will be influenced by functional specialization, which, according to experts, influence the process of globalization.    The analysis of strategies adopted by companies in emerging countries is absolutely necessary because the results cannot be overlooked. For example, until 2004, only five Asian companies were part of the top 100 transnational companies. The study was carried out by UNCTAD and the identification criterion was the size of foreign assets. In 2006, 14% of world total FDI came from emerging countries.    In the global economic crisis, foreign investment flow analysis is a dynamic element that can help the economy of a country. This is not the first time when the world economy is facing recession, but it happens after many years, namely after the Great Depression that began in 1929 and after Breton Woods System Fall in 1971. In addition, we can say that it is for the first time after a long period when the crisis is located at the level of developed countries, not only in emerging economies.    The FDI expansion is indeed a fabulous one, aspects of their development periods of time are presented in detail in this paper. In the last decades of the twentieth century, international investment flows have risen to unprecedented growth. The climax was reached in 2000, next period representing a regression of foreign investments. From 2003 to 2007, it was a period marked by a continuous expansion and increase flows until 2008, when the global economical crisis has had an impact on the entire world economy, including foreign direct investments.    Undoubtedly, the world economic crisis had a negative effect on FDI. The negative impact mostly consisted of two elements, namely: reducing access to financial resources, which affected the ability of firms to invest, and the tendency of companies to invest because of gloomy prospects for the economy, markets and risks.